1997
DOI: 10.1086/303621
|View full text |Cite
|
Sign up to set email alerts
|

The 492 GHz Atmospheric Opacity at the Geographic South Pole

Abstract: We present narrow-bandwidth submillimeter-wave sky opacity measurements made from the South Pole between 1995 February 9 and November 17, a period that includes an entire Austral winter. These measurements were made with the Antarctic Submillimeter Telescope and Remote Observatory (AST/RO) using a heterodyne receiver tuned to a band that includes the 492 GHz Ðne-structure line of neutral atomic carbon. The zenith optical depth was below 0.72 half the time during the Austral winter and spring, and it reached va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 7 publications
6
60
1
Order By: Relevance
“…Schneider et al 2009;Tremblin et al 2011;Matsushita et al 1999;Peterson et al 2003) have already shown that a few sites are well-suited to submm/mid-IR, and FIR-astronomy and their transmission properties are rather well determined (for example by Fourier transform spectrometer obervations in the 0.5-1.6 THz range at Mauna Kea/Hawaii; Pardo et al 2001). The high-altitude (>5000 m) Chilean sites are known for dry conditions (see Matsushita et al 1999;Peterson et al 2003), and site testing is now being carried out at the driest place on Earth, Antarctica (see Chamberlin et al 1997;Yang et al 2010;Tremblin et al 2011). Comparisons between Antarctic and Chilean sites are difficult and uncertain since they rely on ground-based instruments that use different methods and calibration techniques (see Peterson et al 2003, for example).…”
Section: Introductionmentioning
confidence: 99%
“…Schneider et al 2009;Tremblin et al 2011;Matsushita et al 1999;Peterson et al 2003) have already shown that a few sites are well-suited to submm/mid-IR, and FIR-astronomy and their transmission properties are rather well determined (for example by Fourier transform spectrometer obervations in the 0.5-1.6 THz range at Mauna Kea/Hawaii; Pardo et al 2001). The high-altitude (>5000 m) Chilean sites are known for dry conditions (see Matsushita et al 1999;Peterson et al 2003), and site testing is now being carried out at the driest place on Earth, Antarctica (see Chamberlin et al 1997;Yang et al 2010;Tremblin et al 2011). Comparisons between Antarctic and Chilean sites are difficult and uncertain since they rely on ground-based instruments that use different methods and calibration techniques (see Peterson et al 2003, for example).…”
Section: Introductionmentioning
confidence: 99%
“…After the first summer measurements (Dragovan et al 1990;Pajot et al 1989) the Antarctic Submillimetre Telescope and Remote Observatory (AST/RO) was installed at the South Pole (Stark et al 2001). However, while the South Pole has indeed proven to be an exceptionally good site (Chamberlin 2001;Chamberlin, Lane, & Stark 1997), other sites on the Antarctic Plateau could provide still better transparencies and lower atmospheric emission and fluctuations at this and at other wavelength regions, as they feature an higher elevation and are located on the top of a dome where katabatic (gravity-driven) winds, and consequently atmospheric turbulence, are expected to be much lower. Among these sites are Dome C (75 • 05 S, 123 • 06 E, alt.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows 5 months of Pre-HEAT submillimeter opacities, demonstrating the exceptional stability and extremely favorable conditions of the site. The seasonal opacity trends echo those seen at the South Pole (Chamberlin et al 1997): the best conditions are typically observed in late winter and early spring, and generally accompany conditions of low atmospheric pressure (550 mbar, a pressure altitude of 4700 m), calm surface winds (denoted by a strong radiative cooling gradient at the surface), and cold surface temperatures (À80°C).…”
Section: Observationsmentioning
confidence: 61%